2011
DOI: 10.1007/s10729-011-9151-1
|View full text |Cite
|
Sign up to set email alerts
|

Using discrete event simulation to design a more efficient hospital pharmacy for outpatients

Abstract: We present the findings of a discrete event simulation study of the hospital pharmacy outpatient dispensing systems at two London hospitals. Having created a model and established its face validity, we tested scenarios to estimate the likely impact of changes in prescription workload, staffing levels and skill-mix, and utilisation of the dispensaries' automatic dispensing robots. The scenarios were compared in terms of mean prescription turnaround times and percentage of prescriptions completed within 45 min. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…The results of a study in a hospital inpatient pharmacy in Malaysia (47) showed a sharp decrease in patients’ waiting time by adding an extra person for receiving prescriptions at the beginning of the service delivery process, which is consistent with the results of current study. In another study, the results showed that there was a significant decrease in the consultation time and total patients’ waiting time if one physician only provided medico-surgical care and another physician provided only dermatological care (24). On the other hand, results of a study (48) showed that prescription filling interruptions and delays can be reduced by employing and hiring appropriate number of employees in the peak periods of referring to the pharmacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a study in a hospital inpatient pharmacy in Malaysia (47) showed a sharp decrease in patients’ waiting time by adding an extra person for receiving prescriptions at the beginning of the service delivery process, which is consistent with the results of current study. In another study, the results showed that there was a significant decrease in the consultation time and total patients’ waiting time if one physician only provided medico-surgical care and another physician provided only dermatological care (24). On the other hand, results of a study (48) showed that prescription filling interruptions and delays can be reduced by employing and hiring appropriate number of employees in the peak periods of referring to the pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of some studies indicate a strong correlation between total customer satisfaction and their satisfaction from drug services (21-23). The main variables determining the waiting times for an outpatient pharmacy include: 1: The model of receiving prescriptions; 2: The sequence of work; 3: The percentage of staff working (on duty); and 4: job interactions among providers working in the pharmacy (24). The Queuing theory is an analytical survey of waiting in queues as a comprehensive and scientific background in the operation management (25).…”
Section: Introductionmentioning
confidence: 99%
“…The discrete event simulation deployed in the example can also be used to address other process-driven problems that are subject to substantial variability and to capacity constraints, and where there is a clear need to prospectively ask “what-if?” and explore the likely impact of any changes. For example, similar techniques have been used to address accident and emergency departments,43 44 45 hospital pharmacies,46 intensive care units47 and diabetic retinopathy screening services 48…”
Section: Discussionmentioning
confidence: 99%
“…In Reynolds et al (2011), the authors presented the findings of a discrete event simulation study of the hospital pharmacy outpatient dispensing systems in two London hospitals. They tested scenarios to estimate the likely impact of changes in prescription workload, staffing levels and skill mix, and utilization of the dispensaries automatic dispensing robots.…”
Section: General Applicationsmentioning
confidence: 99%